Analysis of Exercise and Health-Related Factors Affecting Student Athletes’ Academic Achievement - Rahmadani, Tri; Iyakrus; Bayu, Wahyu Indra; Hartati, Hartati; Pratama, Reza Resah (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2025)
Student athletes face dual demands to achieve academic success while maintaining athletic performance, which requires effective self-management. This study aims to analyze the factors influencing the academic achievement of student athletes at Sriwijaya University, including learning motivation, time management, physical fitness, family support, allowances and incentives, as well as the utilization of the Test Filit application for managing physical fitness data. Academic achievement, measured by Grade Point Average (GPA), served as the dependent variable. This study employed a quantitative approach with a survey design involving active student athletes at Sriwijaya University. Data were collected through structured questionnaires and physical fitness assessments conducted using the Test Filit application. Data analysis was performed using descriptive statistics and multiple linear regression analysis. The results indicate that the academic achievement of student athletes falls within the good to excellent category. Simultaneously, learning motivation, time management, physical fitness, and external support factors significantly influence academic achievement. The findings reveal that learning motivation and effective time management are dominant factors in maintaining stable academic performance, while well-managed physical fitness supports learning concentration and endurance. In addition, the use of the Test Filit application has proven effective in facilitating efficient measurement and management of physical fitness data. In conclusion, academic achievement among student athletes is influenced by a combination of internal and external factors. Institutional support through flexible academic policies, adequate sports facilities, incentive programs, and the integration of digital technology such as the Test Filit application is essential to support a balanced achievement in both academic and athletic domains.